The Effect of Reward and Punishment on Employee Morale at the Bima Regency Office of Women's Empowerment, Child Protection, Population Control and Family Planning (DP3AP2KB) - Nurul Fayatunisyah; Wulandari (Formosa Journal of Sustainable Research, 2023)
This research aims to ascertain how Employee morale is rewarded and punished by the Bima Regency's office of population control, family planning, child protection, and women's empowerment. 36 individuals—all Asn employees—were chosen for the sample using purposive sampling. According to According to the multiple regression test's findings, each unit increase in the reward variable will have a 0.316 influence on work morale while each unit increase in the punishment variable would have a 0.498 influence. impact. 0.58 is the correlation coefficient. indicates that the dependent variable's relationship to the independent variable is only marginal. 33.6% is the coefficient of determination's value. The effects of reward (X1) and punishment (X2) on employee morale (Y). Employee morale, discipline, and a substantial association between them are revealed by the t and F test results.nd prizes